Análisis del proceso de calidad en mediciones mediante la técnica de Bland Altman. - Ardila Duarte, Gerardo
The monitoring of the measurements by the operators, in the quality process, is a crucial step in decision making and uncertainty evaluation, in this article it is shown that errors are discovered through the Bland Altman technique, in those that apparently present a good relationship in measurements of the same variable. The Bland Altman technique is used when there is only one part or evaluation element, and it is desired to know if an operator is standardized and/or if it is consistent with a gold standard. Measuring different parts and working with 2 or more operators implies another context and Gage R&R must be used, which allows evaluating the integrity of the process.